Elatostema agasthyanum (Urticaceae), a new lithophytic species from the southern Western Ghats, India - Jeomol, K.k.; Sunojkumar, P. (Phytotaxa, 2020)
The present article describes and illustrates a new lithophytic species of Elatostema from the southern Western Ghats, India. The new taxon is morphologically similar to the Taiwan species E. strigillosum, but is clearly distinguishable by the characters of stem, leaves, pistillate inflorescence and achenes. Photographs and distribution map of E. agasthyanum are provided for easy identification. A table showing comparison of morphological characters of similar species is also provided.